Use of Project based Learning - Bansode, Mitali M. (Journal of Engineering Education Transformations, 2016)
Every teacher wants to use innovative teaching methods. But sometimes it creates challenges for a teacher to engage and keep continuous student interest in one hour session. By considering this some teachers are using combination of different teaching methods. Project based learning is an effective and enjoyable teaching method which helps teacher to create competencies among students. Project based learning is one of the excellent method to teach management subjects also, because it is effective, participative and enjoyable method to satisfy academic outcomes. This paper focuses on Project based learning as teaching model. For the study MBA II 30 HR specialization students were selected and results taken on basis of student learning and understanding.